Enhancing slow learners' competency skills through e-LAPD using the UDL approach in clinical chemistry learning - Dian Novita; Zelinda Fitri Amalia; Rahmania Fitrah Sari; Muchlis; Rusmini; Findiyani Ernawati Asih (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
The digitalization of chemistry education plays a crucial role in providing equal learning, this study is essential due to the persistent learning gaps experienced by slow learners in digital chemistry instruction. This study investigated the competency development of two slow learners at SMAN 10 Surabaya through the implementation of digital student worksheets (e-LAPD) focused on balancing chemical equations and Nomenclature of Ionic and Covalent bonds, combined with individualized strategies integrated with the UDL strategy delivered via the Liveworksheet platform. Qualitative data from semi-structured interviews and observations were analyzed using NVivo 11, comparing competencies at the start and end of the learning process. This analysis identified three key competencies: explaining scientific phenomena, interpreting data, and analyzing and evaluating scientific evidence. To supplement the qualitative results, pretest and posttest assessments were conducted, revealing significant improvements in competency. Specifically, students showed an average 40% increase in both the DA and E categories when balancing chemical equations. In contrast, for the Nomenclature of Ionic and Covalent bonds, DA scores rose by 80%, while E scores improved by 100%. The findings confirm that the use of e-LAPD with individualized learning strategies effectively promotes competency improvement among slow learners in chemistry education, guiding future instructional development.